2019
DOI: 10.1371/journal.pone.0212119
|View full text |Cite
|
Sign up to set email alerts
|

Primary HIV prevention in pregnant and lactating Ugandan women: A randomized trial

Abstract: Background The ‘Primary HIV Prevention among Pregnant and Lactating Ugandan Women’ (PRIMAL) study aimed to assess the effectiveness of an enhanced HIV counseling intervention for preventing HIV acquisition among HIV-uninfected mothers during pregnancy and throughout the breastfeeding period. Methods We conducted an unblinded randomized control trial between 22 February 2013 and 22 April 2016 to assess the effectiveness of an extended repeat HIV testing and enhanced coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 41 publications
2
20
0
1
Order By: Relevance
“…This qualitative study showed that participants did feel more knowledgeable and empowered to negotiate sex and condom use. While the PRIMAL study did not find a significant statistical effect of the ERHTEC intervention in increasing condom use or in reducing HIV or STI incidence among HIVuninfected pregnant and lactating Ugandan women, condom use did increase significantly over follow-up in both arms and both groups (individually enrolled women or couples) of the study [9]. This is in line with earlier reports on a slow increase of condom use amongst married couples in Uganda [22][23][24].…”
Section: Male Participant Kii Kampalasupporting
confidence: 85%
See 4 more Smart Citations
“…This qualitative study showed that participants did feel more knowledgeable and empowered to negotiate sex and condom use. While the PRIMAL study did not find a significant statistical effect of the ERHTEC intervention in increasing condom use or in reducing HIV or STI incidence among HIVuninfected pregnant and lactating Ugandan women, condom use did increase significantly over follow-up in both arms and both groups (individually enrolled women or couples) of the study [9]. This is in line with earlier reports on a slow increase of condom use amongst married couples in Uganda [22][23][24].…”
Section: Male Participant Kii Kampalasupporting
confidence: 85%
“…The counselling increased understanding among couples, improved communication, and resulted in more joined decision-making including negotiation about sex and condom use. Although no significant differences were found in the quantitative study in either condom use increase or in HIV and STI incidence over follow-up, the low annual HIV incidence rate of 0.278 per 100 women years of follow-up that characterized the entire study cohort of men and women over an average of 21 months of follow-up is in line with the risk reduction effect participants perceived through the EHRTEC intervention [9].…”
Section: Male Participant Kii Kampalamentioning
confidence: 51%
See 3 more Smart Citations